Decision-driven analytics leveraging human intelligence to unlock the power of data - De Langhe, Bart 1982-; Puntoni, Stefano 1975- (Ascent Audio, 2024)
Challenging the conventional wisdom of data-driven decision-making, marketing professors and behavioral scientists Bart De Langhe and Stefano Puntoni argue that many analytics efforts flounder because data analyses are disconnected from the decisions to be made. In their important book, they offer a new approach they call decision-driven analytics. Counterintuitively, they argue that the key to making good decisions with data is to start by putting data in the background. Drawing from their own research and teaching, as well as real-world business cases, De Langhe and Puntoni offer four pillars of decision-driven analytics and guide you around common mistakes that have held back many organizations from using data for impact. In Decision-Driven Analytics, you will learn how to avoid common pitfalls in data-driven decision-making; close the gap between managers and decision-making on one side, and data scientists and data analytics on the other; enhance the impact of data analytics on business outcomes; and think without data to make better decisions. You'll also learn how to prepare for artificial intelligence's impact on data analytics and evaluate the costs and benefits of decision-driven analytics.